PEMERIKSAAN KESEHATAN, PENGOBATAN GRATIS, DAN PELATIHAN FISIK BAGI MASYARAKAT TERDAMPAK PANDEMI COVID-19 PADA ERA NEW NORMAL DI DENPASAR - Juhanna, I.V.; Adiatmika, I.P.G.; Muliarta, I.M.; Wahyuni, N. (Buletin Udayana Mengabdi, 2022)
Health services is one of the important in improving the health status of the Indonesian people, especially Bali. The increase in the incidence of metabolic diseases is associated with an increase in risk factors due to lifestyle changes. General checkup, free medication, and physical training for the Balinese as prevention and early treatment to overcome health problems during the COVID-19 pandemic. The method is health examination services, free medication, and socialization of metabolic disease physical training for the community in Banjar Bekul, Panjer Village, Denpasar. The result of this activity is that some residents suffer from high blood pressure, high random sugar, high cholesterol levels, and high uric acid levels. The conclusion that can be drawn is that the enthusiasm of the community in this health service.   Keywords: non communicable diseases, metabolic diseases, health examination, exercise training.